Understanding the Estimation of Oil Demand and Oil Supply Elasticities - Lutz Kilian (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper examines the advantages and drawbacks of alternative methods of estimating oil supply and oil demand elasticities and of incorporating this information into structural VAR models. I not only summarize the state of the literature, but also draw attention to a number of econometric problems that have been overlooked in this literature. Once these problems are recognized, seemingly conflicting conclusions in the recent literature can be resolved. My analysis reaffirms the conclusion that the one-month oil supply elasticity is close to zero, which implies that oil demand shocks are the dominant driver of the real price of oil. The focus of this paper is not only on correcting some misunderstandings in the recent literature, but on the substantive and methodological insights generated by this exchange, which are of broader interest to applied researchers.
Keywords: Q43; Q41; C36; C52; 330; oil supply elasticity; oil demand elasticity; IV estimation; structural VAR; Bayesian inference; oil price; gasoline price